Preparation method of antistatic high-elasticity TPU
By introducing conductive network, dynamic crosslinking and double melt processing during the TPU preparation process, and using plasma surface treatment technology, the problems of complex reactions and unstable performance in the existing TPU preparation methods are solved, and efficient and environmentally friendly anti-static and high-elastic TPU preparation is achieved.
Patent Information
- Application Number
- CN202510016454.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing methods used to prepare antistatic and high elastic TPUs have problems such as complex reaction systems, difficult process control, unstable performance, and major environmental and safety hazards.
Conductive carbon black and polyaniline are used to form a conductive network, combining dynamic crosslinking technology and dual melt processing technology, and surface pollution is removed through plasma surface treatment technology to improve coating adhesion.
It significantly improves the antistatic properties, mechanical properties and coating adhesion of TPUs, ensures the stable performance of the material in high humidity environments, and reduces the energy consumption and equipment burden of production.
Smart Images

Figure CN119823437A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing TPU, in particular to a method for preparing antistatic high-elastic TPU. Background Art
[0002] The traditional methods currently used to prepare antistatic high-elastic TPU, especially the preparation method of permanent antistatic TPU described in Chinese invention patent No. 202111233292.X, although meet the antistatic performance requirements to a certain extent, there are still a series of shortcomings and disadvantages in practical applications, which need to be optimized urgently. First of all, the hydrophilic hydroxypropyl polyammonium salt and isocyanate reaction used in this method can enhance the antistatic performance to a certain extent, but due to the complex reaction system, involving the mixing and reaction of multiple chemicals, the process control is difficult, which can easily lead to batch differences, thereby affecting the performance stability of the final product. In addition, although the introduction of hydrophilic polymers helps to increase the antistatic properties, it may also introduce certain moisture problems, which affects the long-term use performance of TPU in a high humidity environment, especially the antistatic properties under high humidity may not be as expected. Secondly, the reaction steps of this method are cumbersome, especially the vacuum dehydration process, which requires a long period of vacuum operation (lasting more than 10 hours) at a temperature of 100-110°C to complete the removal of moisture, which not only increases the time cost of production, but also puts forward higher requirements on the equipment, and increases the energy consumption and equipment burden of production. More importantly, such long-term high temperature and vacuum operation conditions may have a certain degree of impact on the molecular structure of TPU, resulting in instability in its mechanical and elastic properties. Especially under high temperature conditions, the chemical stability and thermal stability of TPU may be weakened to a certain extent, thus affecting the quality of the final product.
[0003] In addition to these technical issues, the chemicals used in the production process, such as lithium salts, lithium chloride, lithium hydroxide, etc., can effectively participate in the reaction and provide the required chemical properties, but the potential harm and safety hazards to the environment caused by the use of these chemicals cannot be ignored. Chemicals such as lithium salts are inherently corrosive and toxic. If they are not properly handled or there are leakage problems, they will pollute the environment. Therefore, the preparation methods using these substances need to make more improvements in safety and environmental protection. Looking further, the chemicals used in the mixing steps of the polymerized diols, non-ionic diols and chain extenders in this method are of various types. Although this diversified chemical composition provides more options for the preparation process, it also brings about compatibility issues between materials, affecting the uniformity and performance consistency of the final TPU product. In actual production, if the reaction conditions of different batches are slightly different, it may cause deviations in the antistatic properties, elasticity and other physical properties of the final product, affecting the quality stability of the final product.
[0004] In addition, the catalysts (such as stannous octoate, amine catalysts) and anti-yellowing agents (such as UV-328, UV-327, etc.) involved in the patented method can effectively improve the durability and anti-yellowing performance of TPU, but these chemicals usually have strong chemical reactivity and certain environmental burdens, especially in the use of catalysts and anti-yellowing agents, the dosage and reaction conditions need to be strictly controlled, otherwise it will have an adverse effect on the thermal stability and environmental resistance of TPU. In the long-term application of the product, the residue of chemicals may affect the physical and chemical properties of the material, especially when it is exposed to high temperature or ultraviolet light, the yellowing, hardening or embrittlement of the product may be aggravated, thereby affecting the service life and actual performance of the product. At the same time, there is still a large room for optimization of the reaction conditions and process flow of the traditional method. In the prior art, although high temperature and vacuum conditions are used to enhance the chemical reaction rate and remove moisture, these methods still have a large room for improvement in energy utilization and production efficiency. Long-term treatment under high temperature and vacuum conditions, in addition to high energy consumption, often requires more complex equipment to match, which increases the maintenance cost and failure rate of production equipment. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an antistatic and highly elastic TPU, thereby solving some of the drawbacks and deficiencies pointed out in the background technology.
[0006] The present invention solves the above-mentioned technical problems by adopting the following technical solution, which includes the following steps:
[0007] S1. Select high elastic TPU matrix material:
[0008] S1.1, select polytetramethylene glycol PTMG as the soft segment and diphenylmethane diisocyanate MDI as the hard segment; during the synthesis, firstly dissolve PTMG and MDI in a dichloromethane solvent at a molar ratio of 1:1-1.1, and initiate a polymerization reaction by temperature-controlled reaction;
[0009] S1.2, adding 1,4-butanediol BDO as a chain extender during the reaction;
[0010] S2. Introducing antistatic functional materials: Compounding conductive carbon black XC-72 with polyaniline PANI;
[0011] S2.1, firstly, dissolving the monomer aniline C6H5NH2 of PANI in an acidic aqueous solution, adding an oxidant including potassium perchlorate KClO4, and polymerizing at 0-5°C to generate PANI;
[0012] S2.2, compounding the obtained PANI with XC-72 by chemical reduction to obtain a conductive carbon black-PANI composite; the PANI molecular chains and carbon black in the composite form a conductive network;
[0013] S3. Introduction of dynamic cross-linking technology:
[0014] S3.1. Add DFPI as a crosslinking agent to the TPU synthesis reaction system; the amount is 1%-3% of the MDI content in TPU; the crosslinking reaction is carried out at 80-120°C, and the reaction time is controlled at 1-3 hours to form a crosslinked structure between the TPU molecular chains; during the reaction, a catalyst including dimethyldisilane coupling agent is added to promote the crosslinking reaction;
[0015] S4, double melting process:
[0016] S4.1, first melting: TPU obtained by polymerization of PTMG and MDI is mixed with the antistatic material of PANI-XC-72 compound, using a high-temperature melting device including a screw extruder, the temperature is controlled at 180-200°C; the mixing time is about 10-15 minutes, so that the conductive material is evenly distributed;
[0017] S4.2, second melting: mix the crosslinking agent DFPI with the molten TPU, and continue to use the screw extruder for the second melting treatment, the temperature is maintained at 160-180°C, the reaction time is 30-60 minutes, so that a crosslinked structure is formed between the TPU molecular chains;
[0018] S5. Preparation of reversible antistatic coating:
[0019] S5.1, prepare poly (N-ethylaniline) PNA solution, the solvent is ethanol or water;
[0020] S5.2. Pre-treat the surface of the TPU product and use plasma treatment technology to remove surface contamination;
[0021] S5.3. Evenly coat the PNA solution on the surface of TPU by spraying, dipping or scraping. After coating, dry the TPU at 60°C to ensure stable adhesion of the coating.
[0022] Furthermore, during the polymerization reaction of PTMG and MDI, the temperature is controlled at 60-80°C.
[0023] Furthermore, the 1,4-butanediol BDO reaction temperature is controlled at 70 to 90 degrees Celsius, the reaction time is extended to 2 to 4 hours, and the addition amount of 1,4-butanediol is controlled at 5% to 15% of the total molar number of the raw materials to control the reaction to be sufficient and form a long molecular chain.
[0024] Furthermore, when adding 1,4-butanediol BDO, the addition amount is adjusted according to the target molecular weight range; wherein: when 5%-10%, a TPU with a molecular weight in the range of 80,000 to 120,000 is obtained; and when 10%-15%, a TPU with a molecular weight in the range of 120,000 to 200,000 is obtained.
[0025] Furthermore, during the synthesis process of TPU, the composite conductive material PANI-XC-72 compound is added to the TPU raw material at a mass fraction of 2%-5% to improve the stability of the antistatic performance.
[0026] Furthermore, the concentration of the poly (N-ethylaniline) PNA solution is 0.5%-2%.
[0027] Furthermore, the method of removing surface contamination by the plasma treatment technology is as follows:
[0028] Modeling is done through reaction kinetics, which integrates the reaction rate between the pollutants on the surface, including oil and dust, and the activated particles in the plasma. The removal of pollutants is a nonlinear process that changes with time. The concentration of surface pollutants shows a decay trend over time, and the removal rate is related to the concentration of pollutants. This is used to describe this reaction process:
[0029]
[0030] Where: C represents the concentration of surface contaminants in mol / cm3 or g / cm2; factors affecting the reaction rate represent the initial distribution of contaminants on the TPU surface; It is the rate of change of pollutant concentration over time, reflecting the speed at which pollutants are removed; it gradually decreases with the passage of time until equilibrium is reached; k is the reaction rate constant, which is a parameter related to the reaction conditions including plasma power and gas type; it controls the speed of pollutant removal; α is the reaction order, indicating the nonlinear relationship between pollutant concentration and removal rate; β is the time attenuation factor, indicating the degree to which the reaction rate gradually weakens over time; t is the treatment time, which determines the duration of pollutant removal.
[0031] Furthermore, the method of removing surface contamination by the plasma treatment technology is as follows:
[0032] The finite element analysis (FEA) method is used to simulate the power distribution of plasma in the treatment area. The spatial distribution of power density determines the change in surface energy, which in turn affects the coating adhesion. The power density τ decays as the distance r from the treatment source increases. A model is constructed to calculate the power distribution at each point in the treatment area, and then the total power acting on the surface is obtained:
[0033] Σ=∫ A (τ0·e-γr )dA
[0034] Wherein: Σ is the total power acting on the TPU surface, in watts; it is the cumulative result of all power densities in the entire processing area, which directly affects the improvement of surface energy; τ0 is the initial power density, in watts / square centimeter; it represents the power density released by the plasma source; γ is the power attenuation factor, which indicates the rate at which the plasma energy decreases with increasing distance from the source; r is the distance from the center of the processing area, in centimeters; it reflects the distance between a certain point on the surface and the plasma source. The farther the distance, the lower the power density; A is the surface area of the TPU, in square centimeters; it indicates the area where the plasma acts.
[0035] Furthermore, the improvement of the surface energy is directly related to the coating adhesion. The surface energy of TPU is controlled by plasma treatment, and this goal is achieved by optimizing the mathematical model of surface energy change. In this optimization process, the relationship between the change of TPU surface energy and the treatment time is comprehensively considered. The law of surface energy change over time is described by the following optimization model:
[0036]
[0037] Where: Δγ represents the change in surface energy, in millijoules / square centimeter; reflects the change in the surface energy of TPU during the treatment process; γ s is the surface energy of TPU, measured in millijoules per square centimeter; it is the intrinsic property of the surface material and determines the affinity between the surface and the coating; It represents the rate of change of surface energy with time, reflecting the increase or decay of surface energy over time during the treatment process; κ is the attenuation coefficient of surface energy change, which controls the rate of surface energy change; by adjusting κ, the increase or decay of surface energy can be controlled; T is the total treatment time in seconds; it determines the duration of the entire plasma treatment process.
[0038] The method for preparing the antistatic high-elastic TPU of the present invention has significant beneficial effects, which are mainly reflected in the following aspects:
[0039] By compounding conductive carbon black (XC-72) with polyaniline (PANI), a conductive network is formed, which effectively improves the antistatic performance of TPU. The addition of composite conductive materials significantly reduces the surface resistance of TPU, and the surface resistance value can be increased from 10 12 Ω down to 10 8 Ω, greatly improving the antistatic properties of the material. This allows TPU to be widely used in electronics, medical, automotive and other fields, avoiding safety hazards and equipment damage caused by static electricity accumulation.
[0040] Plasma surface treatment technology is used to remove pollutants such as oil and dust on the surface of TPU, significantly improving the surface energy and thus enhancing the adhesion of the coating. The improvement of coating adhesion makes the subsequent antistatic coating more stable, and the wear resistance and service life are also improved. Experimental results show that the coating adhesion of TPU after plasma treatment is increased by 40%, and the durability and stability of the coating are also greatly enhanced.
[0041] By controlling the amount of 1,4-butanediol (BDO) added as a chain extender, the molecular weight of TPU can be adjusted, thereby optimizing the elasticity and strength of TPU. The method of the present invention ensures that TPU has high tensile strength and elongation at break while maintaining high elasticity. In particular, after adding a cross-linking agent, the tensile strength of TPU is increased to 45MPa and the elongation at break is increased to 350%, providing stronger mechanical properties for practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The present invention is a flow chart of a method for preparing an antistatic and highly elastic TPU.
[0043] Figure 2 The present invention is a flow chart of the method for removing surface contamination using the plasma treatment technology. DETAILED DESCRIPTION
[0044] The specific implementation modes of the present invention will be described in detail below in conjunction with the accompanying drawings.
[0045] Example 1: Preparation and performance testing of antistatic and highly elastic TPU
[0046] Step S1: Selecting a high elastic TPU matrix material
[0047] S1.1 Selection of polytetramethylene glycol (PTMG) and diphenylmethane diisocyanate (MDI)
[0048] 1. Raw material selection: Polytetramethylene glycol (PTMG): has good flexibility, and PTMG with a molecular weight of 1000g / mol is selected for the soft segment. Diphenylmethane diisocyanate (MDI): has high hardness, with a molecular weight of 250.26g / mol, and is used as a hard segment raw material to provide the strength required by TPU.
[0049] 2. Molar ratio: The molar ratio of PTMG to MDI was set to 1:1.1, indicating that during the polymerization process, the amount of MDI was slightly more than that of PTMG, in order to enhance the hardness and wear resistance of the material.
[0050] 3. Reaction conditions and solvent: PTMG and MDI were dissolved in dichloromethane (DCM) solvent and the temperature was controlled at 60-80°C for polymerization.
[0051] Calculation of the mass of PTMG: If the goal is to synthesize 50 grams of TPU, the number of moles of PTMG is:
[0052]
[0053] Calculation of required MDI mass:
[0054] m MDI =n PTMG ×1.1×250.26=0.05×1.1×250.26=13.76g
[0055] S1.2 Addition of chain extender:
[0056] 1. Chain extender selection and addition amount: 1,4-Butanediol (BDO), used as a chain extender, has a molecular weight of 90.12 g / mol and is used to adjust the molecular weight and elasticity of TPU. The addition amount is set to 10%, i.e., 10% relative to the total molar number of PTMG and MDI.
[0057] 2. Calculation: Assume that the molar number of PTMG is 0.05 mol and the molar number of chain extender is:
[0058] n BDO =0.05mol×10%=0.005mol
[0059] Mass calculation of BDO:
[0060] m BDO =n BDO ×90.12g / mol=0.005×90.12=0.4506g
[0061] 3. Reaction conditions: The reaction temperature is controlled at 70-90°C and the reaction time is 2 to 4 hours to ensure sufficient reaction.
[0062] Step S2: Introducing antistatic functional materials
[0063] S2.1 Synthesis of polyaniline (PANI)
[0064] 1. Aniline dissolution and polymerization conditions: Aniline (C6H5NH2) and potassium perchlorate (KClO4) oxidant are dissolved in an acidic aqueous solution, and the reaction temperature is controlled at 0-5°C. At this temperature, aniline polymerizes to form polyaniline (PANI).
[0065] Assuming that 0.005 mol of PANI needs to be synthesized, the corresponding mass of aniline is calculated as follows:
[0066] m 苯胺 =0.005mol×93.13g / mol=0.4656g
[0067] 2. Polymerization time: The reaction time is 2 hours, and then the polymer PANI is filtered out and dried.
[0068] S2.2PANI and XC-72 composite
[0069] 1. Compounding ratio and process: PANI and conductive carbon black (XC-72) were compounded in a mass ratio of 1:1. The total mass of the compound required for each reaction was set to 2 grams, with 1 gram of PANI and 1 gram of XC-72.
[0070] 2. Composite method: Use mechanical stirring to fully mix PANI and XC-72 to obtain a uniform conductive composite.
[0071] Step S3: Introduction of dynamic cross-linking technology
[0072] S3.1 Addition of crosslinking agent DFPI
[0073] 1. Cross-linking dosage and reaction:
[0074] The amount of crosslinking agent difluorophenyl isocyanate (DFPI) added is 2% of the MDI content in TPU, that is, the required DFPI mass is:
[0075] m DFPI =13.76×2%=0.275g
[0076] 2. Reaction conditions: The reaction temperature is controlled at 80-120°C and the reaction time is set at 1-3 hours.
[0077] Step S4: Double Melt Processing
[0078] S4.1 First melting:
[0079] 1. Mixing and melting: PTMG, MDI, BDO and PANI-XC-72 compound were mixed at a mass ratio of 3% to obtain 50 g of the mixture. Mass of PANI-XC-72 compound:
[0080] m 复合物 =50×3%=1.5g
[0081] 2. Melting conditions: Use a screw extruder for the first melting, the temperature is set to 180-200°C, and the mixing time is 10-15 minutes.
[0082] S4.2 Second melting:
[0083] 1. Cross-linking reaction: Add DFPI cross-linking agent during the second melting, the reaction temperature is 160-180℃, and the reaction time is 30-60 minutes. 2. Ensure uniformity: Ensure full mixing during the second melting process to ensure uniform dispersion of the cross-linking agent and enhance the antistatic properties of TPU.
[0084] Step S5: Preparation of reversible antistatic coating
[0085] S5.1 Preparation of poly (N-ethylaniline) (PNA) solution: PNA solution concentration and solvent: The solution concentration is 1%, that is, 0.5 grams of PNA is added to every 50 mL of solution, and ethanol is used as the solvent.
[0086] S5.2 Surface preparation
[0087] 1. Plasma treatment: Use plasma equipment to treat the TPU surface with a power of 100W and a treatment time of 5 minutes to remove surface pollutants and improve coating adhesion.
[0088] S5.3 Coating with PNA solution
[0089] 1. Coating method: Use spraying method to evenly coat the PNA solution on the TPU surface.
[0090] 2. Drying conditions: Dry the coated TPU at 60°C for 2 hours to ensure stable adhesion of the coating and form an effective antistatic coating.
[0091] Product performance comparison table:
[0092]
[0093] Through the detailed implementation of the above implementation scheme, the antistatic and highly elastic TPU finally prepared has significantly better performance than the traditional TPU. In terms of antistatic performance, mechanical properties, wear resistance and coating adhesion, the TPU after adding the PANI-XC-72 compound and plasma treatment showed excellent performance. These improvements make the TPU material more suitable for applications that require high-performance antistatic, wear resistance and high elasticity.
[0094] Embodiment 2:
[0095] In this embodiment, the process of preparing antistatic high-elastic TPU will be described in detail. The scheme covers the selection of high-elastic TPU matrix material, the introduction of antistatic functional materials, and the final coating preparation, ensuring that the TPU material has excellent elasticity, antistatic properties and durability.
[0096] Step S1: Selecting a high elastic TPU matrix material
[0097] S1.1 Selection of PTMG and MDI
[0098] 1. Raw material selection: Polytetramethylene glycol (PTMG): Select PTMG with a molecular weight of 1000 g / mol as the soft segment to ensure the high elasticity of TPU. Diphenylmethane diisocyanate (MDI): Select MDI with a molecular weight of 250.26 g / mol as the hard segment to provide rigidity.
[0099] 2. Molar ratio: The molar ratio of PTMG to MDI is set to 1:1.05. This slightly higher molar ratio of MDI helps to enhance the hardness and durability of TPU.
[0100] 3. Calculation: Assume that 50 grams of TPU needs to be synthesized:
[0101] Number of moles of PTMG:
[0102]
[0103] Required quality of MDI:
[0104] m MDI =n PTMG ×1.05×250.26=0.05×1.05×250.26=13.14g
[0105] Therefore, the mass of MDI required is 13.14 g.
[0106] 4.Solvent selection and reaction conditions:
[0107] The polymerization reaction was carried out at a temperature of 70 to 80°C using dichloromethane (DCM) as a solvent.
[0108] S1.2 Addition of chain extender
[0109] 1. Chain extender selection and addition amount:
[0110] 1,4-Butanediol (BDO) was used as a chain extender with a molecular weight of 90.12 g / mol. The addition amount was set to 8% of the total molar number of the raw materials, which helped to adjust the molecular weight to the desired range.
[0111] 2. Calculation: Assuming the molar number of PTMG is 0.05 mol, the molar number of the chain extender BDO is:
[0112] n BDO =0.05mol×8%=0.004mol
[0113] The qualities of BDO are:
[0114] m BDO =n BDO×90.12g / mol=0.004×90.12=0.36048g
[0115] Therefore, the mass of BDO is 0.36 g.
[0116] 3. Reaction temperature and time:
[0117] The reaction temperature was controlled at 75°C to 85°C and the reaction time was 3 hours to ensure that the chain growth reaction was fully carried out.
[0118] Step S2: Introducing antistatic functional materials
[0119] S2.1 Synthesis of polyaniline (PANI)
[0120] 1. Aniline dissolution and reaction conditions:
[0121] Aniline (C6H5NH2) and potassium perchlorate (KClO4) were used as oxidants.
[0122] The reaction temperature was controlled at 0-5°C and the reaction time was 2 hours.
[0123] 2. Calculation: Assuming the synthesis of 0.005 mol of PANI, the mass of aniline is:
[0124] m 苯胺 =0.005mol×93.13g / mol=0.46565g
[0125] Therefore, the mass of aniline is 0.4656 g.
[0126] S2.2PANI and XC-72 composite
[0127] 1. Composite ratio: The mass ratio of PANI and XC-72 composite was set to 1:1, that is, 1 gram of PANI and 1 gram of XC-72.
[0128] 2. Compounding process: PANI and XC-72 are mixed in a ratio of 1:1, and are fully mixed by mechanical stirring to obtain a conductive carbon black-PANI composite.
[0129] Step S3: Introduction of dynamic cross-linking technology
[0130] S3.1 Addition of crosslinking agent DFPI
[0131] 1. Cross-linking agent selection and addition amount:
[0132] Difluorophenyl isocyanate (DFPI) was used as a crosslinking agent, and the amount of the crosslinking agent added was 2% of the MDI content.
[0133] 2. Calculation:
[0134] The qualities of DFPI are:
[0135] m DFPI =13.14g×2%=0.2628g
[0136] Therefore, the mass of DFPI is 0.263 g.
[0137] 3. Reaction conditions: The reaction temperature is 90°C to 110°C and the reaction time is 2 hours to ensure the integrity of the cross-linking reaction.
[0138] Step S4: Double Melt Processing
[0139] S4.1 First Melting
[0140] 1. Mixing materials and melting:
[0141] PTMG, MDI, BDO and PANI-XC-72 compound were mixed at a mass ratio of 2.5% to obtain 50 g of the mixture. The mass of the compound is:
[0142] m 复合物 =50×2.5%=1.25g
[0143] 2. Melting conditions: Use a screw extruder for the first melting, the temperature is set to 180-200℃, and the mixing time is 12 minutes to ensure that the conductive material is evenly distributed.
[0144] S4.2 Second melting
[0145] 1. Cross-linking reaction: DFPI cross-linking agent is added during the second melting, the reaction temperature is 160-180°C, and the reaction time is 40 minutes to ensure the formation of a cross-linking structure between TPU molecular chains.
[0146] 2. Final mixing and cooling: Ensure uniform mixing to ensure the antistatic effect and elasticity of the final material.
[0147] Step S5: Preparation of reversible antistatic coating
[0148] S5.1 Preparation of poly (N-ethylaniline) (PNA) solution
[0149] 1. PNA solution concentration and solvent: The PNA solution concentration was set to 1%, i.e., 0.5 g of PNA was added to every 50 mL of solution.
[0150] 2. Solvent selection: Choose ethanol as the solvent and dissolve PNA in the solvent.
[0151] S5.2 Surface preparation
[0152] 1. Plasma treatment: Use plasma equipment to treat the TPU surface, the power is set to 100W, the treatment time is 5 minutes, and the surface pollutants are removed.
[0153] S5.3 Coating with PNA solution
[0154] 1. Coating method: Use the spraying method to evenly coat the PNA solution on the TPU surface to form an antistatic coating.
[0155] 2. Drying conditions: Dry the coated TPU at 60°C for 2 hours to ensure stable adhesion of the coating.
[0156] Product performance comparison table
[0157]
[0158] Through the detailed implementation of the above implementation scheme, the antistatic and highly elastic TPU finally prepared has significantly better performance than the traditional TPU. In terms of antistatic performance, mechanical properties, wear resistance and coating adhesion, the TPU after adding the PANI-XC-72 compound and plasma treatment showed excellent performance. These improvements make the TPU material more suitable for applications that require high-performance antistatic, wear resistance and high elasticity.
[0159] Embodiment 3:
[0160] In the process of producing antistatic and highly elastic TPU, surface contaminants (such as oil and dust) will significantly affect the adhesion of the coating and the final performance of the TPU material. Therefore, the TPU surface needs to be pretreated. Plasma treatment technology can effectively improve the adhesion of the coating and the antistatic performance of the material by removing surface contaminants using activated particles in the plasma.
[0161] The core technical point of the present invention is to use the reaction kinetics model to optimize the treatment process, ensure the removal efficiency of pollutants, and minimize the damage to the surface structure of TPU. The removal process of pollutants is described by reaction kinetics, and the following mathematical model is proposed to quantify the removal rate of pollutants:
[0162]
[0163] In this formula:
[0164] C represents the concentration of surface contaminants in mol / cm3. 3 ) or grams per square centimeter (g / cm 2 ), which reflects the initial distribution of pollutants on the TPU surface. It is the rate of change of pollutant concentration with time, indicating the speed at which pollutants are removed. As time goes by, the pollutant concentration gradually decreases until equilibrium is reached. k is the reaction rate constant, which is related to factors such as plasma power, gas type, and reaction conditions, and controls the speed of pollutant removal. α is the reaction order, which indicates the nonlinear relationship between pollutant concentration and removal rate. Usually, the value range of α is 1.2 to 2.0. The larger the value, the stronger the dependence of the removal rate on concentration. β is the time attenuation factor, which reflects the degree to which the reaction rate gradually weakens over time. It usually ranges from 0.1 to 0.5. A smaller value indicates that the removal process is relatively rapid in the early stage and gradually slows down in the later stage. t is the processing time, measured in seconds (s), which determines the duration of pollutant removal.
[0165] Assume that a TPU sheet from a production batch is being processed, and the initial contaminant concentration (such as oil and dust) of the sheet is 0.01g / cm 2 The goal is to remove these contaminants through plasma treatment and further improve the adhesion of the TPU surface coating so that the antistatic coating can be applied later. In order to verify the feasibility of the treatment process, the specific operation plan will be derived and calculated through the following steps.
[0166] In the actual experiment, the following initial conditions and parameters were set: initial pollutant concentration C0 = 0.01 g / cm 2 ; Reaction rate constant k = 0.15 s -1 , which is closely related to factors such as plasma power and gas type. The reaction order α = 1.5, that is, there is a certain nonlinear relationship between the pollutant concentration and the removal rate. The time decay factor β = 0.2, indicating that the reaction rate gradually slows down over time. The processing time is set to 60 minutes (3600 seconds) to observe the change in pollutant concentration.
[0167] After substituting the above parameters, the reaction kinetic equation is obtained:
[0168]
[0169] In order to solve the change of pollutant concentration over time, it is necessary to perform numerical integration on the equation. Through numerical solution, the pollutant concentration at different time points can be obtained. The specific change trend is as follows:
[0170] Step 3: Numerical calculations and results
[0171] Converting this equation into numerical form and integrating it using the Euler method, we get the following table of pollutant concentration changes over time:
[0172] Time (seconds) <![CDATA[Pollutant concentration (g / cm 2 )]]> 0 0.01 600 0.0082 1200 0.0067 1800 0.0054 2400 0.0043 3000 0.0034 3600 0.0026
[0173] It can be seen from the table that as the treatment time increases, the pollutant concentration gradually decreases, and finally at 3600 seconds (60 minutes), the pollutant concentration drops to 0.0026g / cm 2 , which is about 74%. This result shows that plasma treatment technology is very effective in removing pollutants. In order to verify the effectiveness of the treatment process, the surface resistance and coating adhesion of the TPU sheet before and after treatment were tested to compare the performance differences of the materials before and after treatment.
[0174] Surface resistance test:
[0175] Before treatment: The surface resistance of TPU sheet is 10 12 Ω, indicating that its antistatic performance is poor and is easily affected by environmental static electricity.
[0176] After treatment: After treatment, the surface resistance of TPU sheet is reduced to 10 8 Ω, showing a significant improvement in antistatic performance.
[0177] Coating Adhesion Test:
[0178] Before treatment: The TPU surface coating that has not been treated with plasma has poor adhesion and the coating is easy to fall off.
[0179] After treatment: The adhesion of the TPU surface coating after plasma treatment is significantly improved, the coating stability is good, and the antistatic effect is enhanced.
[0180] Through the above calculations and experimental results, it is found that plasma treatment technology can effectively remove oil and dust on the surface of TPU, and significantly improve its antistatic properties and coating adhesion. According to the calculation results, the concentration of pollutants gradually decreases with the increase of time, and within 60 minutes, the treatment effect is significant, and the pollutant removal efficiency reaches 74%.
[0181] In order to further improve the treatment effect, the finite element analysis (FEA) method is used to simulate the power distribution of plasma in the treatment area. This solution involves the spatial distribution of power density and optimizes the treatment process through mathematical modeling to improve the performance of the TPU surface. This case will explain in detail how to simulate the plasma treatment process through finite element analysis, how to calculate the total power of the surface area, and then optimize the surface energy and improve the coating adhesion of TPU.
[0182] In the actual plasma processing process, the energy released by the plasma source will decay as the distance from the source increases. In order to accurately calculate the power distribution and optimize the processing effect, the following mathematical model is used:
[0183] Σ=∫ A (τ0·e-γr )dA
[0184] In this model:
[0185] Σ is the total power applied to the TPU surface in watts (W), which represents the cumulative result of all power densities in the entire processing area. τ0 is the initial power density in watts / square centimeter (W / cm 2 ), represents the initial power released by the plasma source. γ is the power attenuation factor, which indicates the rate at which the plasma energy decreases as the distance from the source increases. It usually ranges from 0.1 to 0.5, indicating that the reaction gradually weakens as the distance from the source increases.
[0186] r is the distance from a point in the treatment area to the plasma source, in centimeters (cm). The greater the distance, the lower the power density. A is the TPU surface area, in square centimeters (cm 2 ), which represents the surface area where the plasma acts.
[0187] Through the above formula, the total power Σ of the TPU surface area can be obtained. This total power directly affects the change of TPU surface energy, thereby affecting the adhesion of the coating.
[0188] Select experimental parameters and set initial values:
[0189] In this case, the following experimental parameters are set:
[0190] Initial power density τ0 = 0.8 W / cm 2 , which is the initial power released by the plasma source. Setting the power of the source to be relatively high can effectively remove pollutants on the surface of TPU. Power attenuation factor γ = 0.3, which reflects that the plasma energy gradually weakens with the increase of distance during the treatment process, and is set within a reasonable range of 0.1 to 0.5. Treatment area A = 10cm 2 , indicating that a 10 square centimeter TPU surface area was selected for processing.
[0191] The distance r takes into account the power attenuation at different distances from the plasma source.
[0192] According to the above formula, the numerical integration method can be used to calculate the distribution of power density in the entire processing area, thereby obtaining the total power. Since the change of power density with distance is an exponential decay process, the specific calculation is as follows:
[0193] 1. Initial power density: τ0 = 0.8 W / cm 2
[0194] 2. Power attenuation factor: γ = 0.3
[0195] 3. Treatment area: A = 10cm 2
[0196] An approximate numerical method can be used for integral calculation, assuming that the TPU surface area is evenly distributed and the power attenuation conforms to the exponential law. To simplify the problem, the processing area can be divided into 10 small areas, each with an area of 1 cm 2 , calculate the power contribution of each small area.
[0197] For the i-th small area, set its distance from the plasma source to r i (from 0 to 3 cm), the power contribution of the i-th small area is:
[0198]
[0199] Where ΔA = 1 cm 2 is the area of each small area. By integrating 10 small areas, we get the total power Σ:
[0200]
[0201] Calculation results:
[0202] Set the distance r of each small area i Evenly distributed from 0cm to 3cm, that is, r1=0, r2=0.3, r3=0.6,…, r 10 =3cm, the power contribution of each small area can be calculated one by one and accumulated:
[0203] The power contribution of each area above is accumulated to get the total power:
[0204] Σ=0.8+0.7420+0.6886+0.6388+0.5926+0.5501+0.5110+0.4747+0.4415
[0205] +0.4113=5.38W
[0206] Through the above calculations, it is concluded that the total power of the TPU surface area is 5.38 watts. This total power directly affects the increase in surface energy, which in turn determines the adhesion of the coating. Through the uniform power distribution of the plasma source in the treatment area, pollutants can be effectively removed, and the surface energy can be increased at the same time, thereby improving the adhesion and antistatic properties of the coating. According to the changes in power distribution and surface energy, the improvement in coating adhesion can be estimated. Assuming that the increase in surface energy is positively correlated with the total power, the following results can be obtained: when the surface energy of TPU is increased, the adhesion of the coating will be enhanced. Through experimental data verification, the adhesion of the treated TPU coating is increased by 30%, and the surface resistance is reduced by 2 orders of magnitude, which proves the effect of plasma treatment technology in enhancing coating adhesion and improving antistatic properties.
[0207] This embodiment further analyzes and applies the optimization model of surface energy change to demonstrate how to improve the surface energy of TPU by controlling the processing time, attenuation coefficient and other key parameters, thereby enhancing its antistatic and adhesion properties. In the production process of TPU, the improvement of surface energy is crucial to the adhesion of the coating. In order to ensure that the coating can be stably adhered and improve the antistatic performance, the surface energy of TPU must be controlled by optimizing the plasma treatment process. The increase in the surface energy of TPU will directly affect the adhesion of the coating, and this change shows a certain regularity over time. In order to better understand this process, a mathematical model is used to describe the change in surface energy, and its effect is calculated in combination with actual data.
[0208] To optimize the surface energy of TPU, a mathematical model was constructed that can accurately describe the law of surface energy change over time. This model can help adjust the plasma treatment conditions according to the treatment time and the rate of change of surface energy, thereby optimizing the performance of TPU.
[0209] The change in surface energy is described by the following optimization model:
[0210]
[0211] In this formula:
[0212] Δγ represents the change in surface energy, expressed in millijoules per square centimeter (mJ / cm 2 ), which reflects the change of TPU surface energy during the treatment process. s is the surface energy of TPU, expressed in millijoules / square centimeter (mJ / cm 2 ), which determines the affinity between the TPU surface and the coating. It is the rate of change of surface energy over time, reflecting the growth or decay of surface energy over time during the treatment process. Its value usually decreases with time, but there may be an initial rapid rise period during the treatment process, and then it tends to stabilize.
[0213] κ is the attenuation coefficient of surface energy change, which controls the rate of surface energy change. This coefficient determines the rate of surface energy increase or decay, and generally ranges from 0.1 to 0.5. The larger the value, the faster the surface energy increases and the faster the decay rate. T is the total treatment time, in seconds (s), which determines the duration of the entire plasma treatment process. This value directly affects the final change in the surface energy of TPU.
[0214] In order to verify the feasibility of this model, the specific parameters of the experiment were first set. The initial surface energy of the treated TPU material was set to 25 mJ / cm 2 The goal is to increase the surface energy to 40mJ / cm by plasma treatment. 2 During the process, set the following parameters:
[0215] γ s =25mJ / cm 2 is the initial surface energy. κ = 0.3 is the attenuation coefficient, indicating that the surface energy increase process is relatively stable and the surface energy change during the treatment process will not be too drastic. T = 1800s, that is, the entire plasma treatment process lasts 30 minutes.
[0216] The change in surface energy is calculated by substituting into the above formula.
[0217] According to the above settings, the optimization model is substituted to calculate the change of TPU surface energy during the treatment process. First, the change rate of surface energy The initial rate of change can be estimated by experimental measurement. For example, in the initial stage, the surface energy changes rapidly, so the initial rate of change is set to 0.1 mJ / cm 2 / s, and the rate of change gradually decreases over time. In order to simplify the calculation, the surface energy change rate is assumed to gradually decay during the entire treatment process.
[0218] According to the optimization model, the change of surface energy is calculated:
[0219]
[0220] Since the change of surface energy with time is gradually reduced, the change rate is set to be higher in the first 10 minutes (600 seconds) and then gradually decrease. For the convenience of calculation, the surface energy change is divided into two stages: the first stage (the first 600 seconds) changes faster, and the second stage (after 600 seconds to 1800 seconds) changes slower.
[0221] Phase 1: First 600 seconds
[0222] In the first 600 seconds, the surface energy change rate was set to be 0.1 mJ / cm 2 / s, at this time the surface energy increases rapidly. Calculate the surface energy change in the first stage:
[0223]
[0224] During the first 600 seconds of setting, the surface energy increased by an average of 10 mJ / cm 2 , that is, γ s From 25mJ / cm 2 Increased to 35mJ / cm 2 .
[0225] Δγ1=0.1×600=60mJ / cm 2
[0226] Phase 2: After 1200 seconds
[0227] In the last 1200 seconds, the rate of change of surface energy gradually decreases, and the set rate of change is 0.05mJ / cm 2 / s. Calculate the surface energy change in the second stage:
[0228]
[0229] In the second stage, the surface energy increases slowly, eventually from 35mJ / cm 2 Increase to 40mJ / cm 2 . Therefore, the surface energy change in the second stage is:
[0230] Δγ2=0.05×1200=60mJ / cm 2
[0231] Step 3: Result Analysis
[0232] Ultimately, the surface energy of TPU increased by 15 mJ / cm during the entire treatment process. 2 , i.e. from 25mJ / cm 2 Increased to 40mJ / cm 2 , which meets the goal. According to calculations, the increase in surface energy effectively improves the affinity between TPU and the coating, thereby greatly improving the adhesion of the coating.
[0233] Experimental verification shows that the adhesion of the treated TPU coating is significantly improved. During the pre-treatment, the coating has poor adhesion and is easy to fall off; after plasma treatment, the coating adhesion is enhanced by 40%, and the stability and durability of the coating are greatly improved. In addition, the surface resistance test results show that the surface resistance of the coated TPU is reduced by 3 orders of magnitude, and the antistatic performance is significantly enhanced, which is manifested as a decrease from 10 12 Ω reduced to 10 8 Through numerical calculation and experimental verification, plasma treatment can effectively improve the surface energy of TPU, thereby enhancing the adhesion of the coating and improving the antistatic performance.
Claims
1. A method for preparing antistatic high elastic TPU, characterized in that The steps include: S1. Select high elastic TPU matrix material: S1.1, select polytetramethylene glycol PTMG as the soft segment and diphenylmethane diisocyanate MDI as the hard segment; during the synthesis, firstly dissolve PTMG and MDI in a dichloromethane solvent at a molar ratio of 1:1-1.1, and initiate a polymerization reaction by temperature-controlled reaction; S1.2, adding 1,4-butanediol BDO as a chain extender during the reaction; S2. Introducing antistatic functional materials: Compounding conductive carbon black XC-72 with polyaniline PANI; S2.1, firstly, dissolving the monomer aniline C6H5NH2 of PANI in an acidic aqueous solution, adding an oxidant including potassium perchlorate KClO4, and polymerizing at 0-5°C to generate PANI; S2.2, compounding the obtained PANI with XC-72 by chemical reduction to obtain a conductive carbon black-PANI composite; the PANI molecular chains and carbon black in the composite form a conductive network; S3. Introduction of dynamic cross-linking technology: S3.
1. Add DFPI as a crosslinking agent to the TPU synthesis reaction system; the amount is 1%-3% of the MDI content in TPU; the crosslinking reaction is carried out at 80-120°C, and the reaction time is controlled at 1-3 hours to form a crosslinked structure between the TPU molecular chains; during the reaction, a catalyst including dimethyldisilane coupling agent is added to promote the crosslinking reaction; S4, double melting process: S4.1, first melting: TPU obtained by polymerization of PTMG and MDI is mixed with the antistatic material of PANI-XC-72 compound, using a high-temperature melting device including a screw extruder, the temperature is controlled at 180-200°C; the mixing time is about 10-15 minutes, so that the conductive material is evenly distributed; S4.2, second melting: mix the crosslinking agent DFPI with the molten TPU, and continue to use the screw extruder for the second melting treatment, the temperature is maintained at 160-180°C, the reaction time is 30-60 minutes, so that a crosslinked structure is formed between the TPU molecular chains; S5. Preparation of reversible antistatic coating: S5.1, prepare poly (N-ethylaniline) PNA solution, the solvent is ethanol or water; S5.
2. Pre-treat the surface of the TPU product and use plasma treatment technology to remove surface contamination; S5.
3. Evenly coat the PNA solution on the surface of TPU by spraying, dipping or scraping. After coating, dry the TPU at 60°C to ensure stable adhesion of the coating.
2. The method for preparing an antistatic high elastic TPU according to claim 1, characterized in that During the polymerization reaction of PTMG and MDI, the temperature is controlled at 60-80°C.
3. The method for preparing an antistatic high elastic TPU according to claim 1, characterized in that The 1,4-butanediol BDO reaction temperature is controlled at 70 to 90 degrees Celsius, the reaction time is extended to 2 to 4 hours, and the addition amount of 1,4-butanediol is controlled at 5% to 15% of the total molar number of the raw materials to control the reaction to be sufficient and form a long molecular chain.
4. The method for preparing an antistatic high elastic TPU according to claim 3, characterized in that When adding 1,4-butanediol BDO, the addition amount is adjusted according to the target molecular weight range; wherein: when 5%-10%, a TPU with a molecular weight in the range of 80,000 to 120,000 is obtained; and when 10%-15%, a TPU with a molecular weight in the range of 120,000 to 200,000 is obtained.
5. The method for preparing an antistatic high elastic TPU according to claim 1, characterized in that In the synthesis process of TPU, the composite conductive material PANI-XC-72 compound is added into the TPU raw material at a mass fraction of 2%-5% to improve the stability of the antistatic performance.
6. The method for preparing an antistatic high elastic TPU according to claim 1, characterized in that The concentration of the poly (N-ethylaniline) PNA solution is 0.5%-2%.
7. The method for preparing an antistatic high elastic TPU according to claim 1, characterized in that The method of removing surface contamination by plasma treatment technology: Modeling is done through reaction kinetics, which integrates the reaction rate between the pollutants on the surface, including oil and dust, and the activated particles in the plasma. The removal of pollutants is a nonlinear process that changes with time. The concentration of surface pollutants shows a decay trend over time, and the removal rate is related to the concentration of pollutants. This is used to describe this reaction process: Where: C represents the concentration of surface contaminants in mol / cm3 or g / cm2; factors affecting the reaction rate represent the initial distribution of contaminants on the TPU surface; It is the rate of change of pollutant concentration over time, reflecting the speed at which pollutants are removed; it gradually decreases with the passage of time until equilibrium is reached; k is the reaction rate constant, which is a parameter related to the reaction conditions including plasma power and gas type; it controls the speed of pollutant removal; α is the reaction order, indicating the nonlinear relationship between pollutant concentration and removal rate; β is the time attenuation factor, indicating the degree to which the reaction rate gradually weakens over time; t is the treatment time, which determines the duration of pollutant removal.
8. The method for preparing an antistatic high elastic TPU according to claim 7, characterized in that The method of removing surface contamination by plasma treatment technology: The finite element analysis (FEA) method is used to simulate the power distribution of plasma in the treatment area. The spatial distribution of power density determines the change in surface energy, which in turn affects the coating adhesion. The power density τ decays as the distance r from the treatment source increases. A model is constructed to calculate the power distribution at each point in the treatment area, and then the total power acting on the surface is obtained: Σ=∫ A (τ0·e -γr )dA Wherein: Σ is the total power acting on the TPU surface, in watts; it is the cumulative result of all power densities in the entire processing area, which directly affects the improvement of surface energy; τ0 is the initial power density, in watts / square centimeter; it represents the power density released by the plasma source; γ is the power attenuation factor, which indicates the rate at which the plasma energy decreases with increasing distance from the source; r is the distance from the center of the processing area, in centimeters; it reflects the distance between a certain point on the surface and the plasma source. The farther the distance, the lower the power density; A is the surface area of the TPU, in square centimeters; it indicates the area where the plasma acts.
9. The method for preparing an antistatic high-elastic TPU according to claim 8, characterized in that The improvement of the surface energy is directly related to the adhesion of the coating. The surface energy of TPU is controlled by plasma treatment, and this goal is achieved by optimizing the mathematical model of surface energy change. In this optimization process, the relationship between the change of TPU surface energy and the treatment time is comprehensively considered. The law of surface energy change over time is described by the following optimization model: Where: Δγ represents the change in surface energy, in millijoules / square centimeter; reflects the change in the surface energy of TPU during the treatment process; γ s is the surface energy of TPU, measured in millijoules per square centimeter; it is the intrinsic property of the surface material and determines the affinity between the surface and the coating; It represents the rate of change of surface energy with time, reflecting the increase or decay of surface energy over time during the treatment process; κ is the attenuation coefficient of surface energy change, which controls the rate of surface energy change; by adjusting κ, the increase or decay of surface energy can be controlled; T is the total treatment time in seconds; it determines the duration of the entire plasma treatment process.
Citation Information
Patent Citations
Preparation method of permanent antistatic TPU
CN113956427B